1995
DOI: 10.1172/jci117916
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of the growth hormone and insulin-like growth factor-I axis to chronic and severe calorie or protein malnutrition.

Abstract: The hierarchy of diet components (e.g., protein, carbohydrate, vitamins, and minerals) influencing growth hormone (GH), insulin-like growth factor-I (IGF-I), and their binding proteins (BP) is not well defined. Young adult rats were fed diets for 1 mo that included low protein or 60% and 40% of carbohydrate calories. We hypothesized that levels of both hormones, their dominant BPs and liver IGF-I mRNA would fall, and that part of the mechanism for decreasing serum IGF-I would be enhanced IGFBP-3 protease activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(65 citation statements)
references
References 55 publications
3
60
0
2
Order By: Relevance
“…Energy restriction to 40% of maintenance decreased IGFBP-3 concentrations in young rats (Oster et al 1995), whereas IGFBP-2 concentrations increased after only 4 days of similar dietary modification in meat-type chickens (Kitka et al 1996). In adult human volunteers, IGFBP-3 was decreased and IGFBP-2 increased by short-term restriction of protein, and subsequently normalised with refeeding (Smith et al 1995).…”
Section: Discussionmentioning
confidence: 93%
“…Energy restriction to 40% of maintenance decreased IGFBP-3 concentrations in young rats (Oster et al 1995), whereas IGFBP-2 concentrations increased after only 4 days of similar dietary modification in meat-type chickens (Kitka et al 1996). In adult human volunteers, IGFBP-3 was decreased and IGFBP-2 increased by short-term restriction of protein, and subsequently normalised with refeeding (Smith et al 1995).…”
Section: Discussionmentioning
confidence: 93%
“…The IGF axis, one of the major regulators of growth, both pre-and postnatally (Randhawa and Cohen, 2005), can be profoundly altered by malnutrition in utero (Estívariz and Ziegler, 1997). This can reduce concentrations of both circulating IGF-1 and growth hormone (Oster et al, 1995). Finally, elevated stress levels during pregnancy may cause growth retardation in the foetus (Liu et al, 1993;Kranendonk et al, 2006;Diego et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We found that the pattern of expression is different among the different lymphoid tissues studied, as well as, among the various cell subsets. It is well known that fasting or protein calorie malnutrition decreases the GHR expression in the liver causing a resistance to the growth hormone action; less severe malnutrition such as a decreased protein intake, does not affect the GH binding but some post-receptors defects have been described (11,13). In this study of protein deprivation at various levels, an increase in the GHR binding has been observed.…”
Section: Discussionmentioning
confidence: 64%
“…Both protein and energy intake are critical in the regulation of serum levels of IGF-I, IGF binding protein-3 (IGFBP-3), IGF binding protein-1 (IGFBP-1), GH and GH binding protein (GHBP), as well as the expression levels of the GHR and the IGF-I receptor (IGF-IR) (8)(9)(10). It is known that a GH resistant state is induced during nutritional stress, depending on the specific type and length of nutrient deprivation (11). In humans and in several other species, when food intake is reduced, serum GH levels are increased (except in the rat) and circulating levels of IGF-I, IGFBP-3 and GH-BP are reduced (11,13).…”
mentioning
confidence: 99%
See 1 more Smart Citation